Design and Development of Amperometric Universal Glucose Meter System for Different Testing Strips - Paglinawan, Arnold; Cruz, Febus Reidj; Paglinawan, Charmaine; Alcantara, Ashley Alyssa; Orival, Jude Benson; Palomaria, Ardie A.; Paras, Angel Rupert; Chung, Wen Yaw (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The purpose of this study is to design and develop a universal glucose meter device that could analyze different brands of testing strips. The functionality of the universal glucose meter is based on switching matrix and microcontroller .A small amount of current produced by the reaction of the blood sample with the glucose oxidase from the testing strips and it is used as its input. The input current will be incorporated into a signal conditioning circuit and it will be converted in terms of voltage, which will serve as input for the microcontroller. The microcontroller unit will allow the read and analyze the voltage level of the blood sample and by using an equation obtained from the calibration of the testing strips, the glucose level is converted to mg/dL unit. A series of tests were performed to compare the results obtained from the designed universal glucose meter and the corresponding test strip. Overall, the test using the universal glucose meter showed acceptable accuracy. The development of this universal glucose meter will assist diabetic patients and clinics for testing glucose level using various testing strips on a single device.